Pemetaan Potensi Karbon Biru pada Kawasan Mangrove di Kabupaten Kayong Utara - Adityo Raynaldo; Robin Saputra; Zan Zibar (Jurnal Kelautan Tropis, 2024)
Distribution and extent of existing mangroves, conditions, and potential for blue carbon are needed to encourage the economy of coastal communities as coastal ecosystem services. Kayong Utara Regency as one of the regencies in the coastal area of West Kalimantan has the potential for mangroves to be utilized by coastal communities but there has been no ecological study of the potential for blue carbon contained therein. This study aims to map the distribution of mangroves and their conditions and to map the spatial distribution of mangrove carbon stocks in the Kayong Utara Regency. The mapping method for the distribution of existing mangroves is carried out using the visual interpretation method by making a certain false-color RGB composite, the distribution of mangroves is identified using nine key elements of image interpretation. Mangrove conditions were analyzed through mangrove cover using the hemispherical photography method. Mapping of carbon stocks was carried out using a linear regression model formulation of several vegetation index variables and carbon stock values from making observation plots, then analyzed spatially. The research results show that the mangrove area in North Kayong Regency is 20,543.40 ha, spread throughout the district. Mangrove conditions consist of the categories rare 3.92%, moderate 53.07%, and dense 43.01%. Tree density (DBH ≥ 10 cm) from 56 survey points ranged from 100 – 2800 individual ha-1 with AGC values ranging from 4.21 – 1375.74 Mg ha-1. The dominant mangrove species found included Avicennia alba, A. lanata, A. marina, Bruguiera parviflora, Excoecaria agallocha, Rhizophora apiculata, R. mucronata, R. stylosa, Xylocarpus granatum. The best linear regression model in this study uses the MDI2 variable with the formulation y = 225.08x – 114.55 and the Pearson correlation value (r) = 0.377. The AGC potential value of the selected model ranges from 0 – 631.92 Mg ha-1 spread with the largest potential value found in Pulau Maya District.